Schematic Analysis of P10 16x32 RGB LED Panel 3 in 1 DIP Type Dual (Dual In-Line Package) on Trafficlight Revolution - Putra S D; Endra R Y (Bandar Lampung University (UBL), 2017)
The issue of transportation in various forms is one of the main problems faced by the world's cities, including cities in Indonesia. Growth in the vehicle, increasing the intensity of the traffic of goods andservices as well as increased user population associated disproportionate availability of roads and supporting facilities resulted in a wide range of crucial issues. Traffic congestion is one of the mainproblems in the transportation system. Coupled with the specific transportation community awareness so that adds a level of congestion becomes worse. Signs and traffic lights play an important role inregulating the traffic lane so that the public transport can be wise in using the road, especially in city traffic Bandar Lampung (according to Law no. 22/2009 on Traffic and Transportation: tool signalingtraffic or APILL) are lights that control traffic flow that is attached at a crossroads, pedestrian crossings (zebra crossing), and the flow of other traffic. In this issue resolve conducted a study oftraffic lights (trafficlight) that exist today. With the aim to build a traffic light system which only uses LED panel (Light Emitting Diode). Where to control the color and symbol lights can be setautomatically using a microcontroller to change color, and in complete text runs to update the traffic so that traffic lights easier to understand and informative. For that I am interested to analyze theworkings of Led Panel Schematic, such as what and how.